Credit Rating Agency and Equity Analysts’ Adjustments to GAAP Earnings - Batta, George; Muslu, Volkan (Contemporary Accounting Research, 2017)
Abstract Moody's analysts and sell‐side equity analysts adjust GAAP earnings as part of their research. We show that adjusted earnings definitions of Moody's analysts are significantly lower than those of equity analysts when companies exhibit higher downside risk, as measured by volatility in idiosyncratic stock returns, volatility in negative market returns, poor earnings, and loss status. Relative to the adjusted earnings definitions of equity analysts, adjusted earnings definitions of Moody's analysts better predict future bankruptcies, yet they fare significantly worse in predicting future earnings and operating cash flows. These findings persist after controlling for optimism incentives of analysts, reporting incentives of companies, credit rating levels, and industry and year effects. Our findings suggest that credit rating agencies cater to their clients’ demand for a more conservative interpretation of company‐reported performance than what is offered by equity analysts.